2012
DOI: 10.1115/1.4004729
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Effects of a Large Recirculating Area on the Performance of an Effusion Cooled Combustor Liner

Abstract: An experimental analysis of a realistic engine cooling scheme was performed on a test article replicating a slot injection and an effusion array with a central large dilution hole. A test section consists of a rectangular cross-section duct with a flat plate comprised of 270 effusion holes arranged in 29 staggered rows (D = 1.65 mm, Sx/D = 7.6, Sy/D = 6, L/D = 5.5, α = 30 deg) and a dilution hole (D = 18.75 mm) located at the 14th row. Both effusion and dilution holes are fed by a channel replicating a combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The following equation is to determine the effectiveness of film-cooling. (6) Here , and is the local temperature, the temperature mainstream and coolant respectively. Table 2 provides a list of parameters used in the governing equations for solving the problem.…”
Section: Methodology 21 Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following equation is to determine the effectiveness of film-cooling. (6) Here , and is the local temperature, the temperature mainstream and coolant respectively. Table 2 provides a list of parameters used in the governing equations for solving the problem.…”
Section: Methodology 21 Model Descriptionmentioning
confidence: 99%
“…Another finding by Bernsdorf et al, [5] showed that in short cooling injection holes, effectiveness of film cooling is related to the injection hole length and angle. Tarchi et al [6] investigated the effects of large dilution holes. These holes were placed within the injecting slot and eruption array.…”
Section: Introductionmentioning
confidence: 99%
“…The study has been reported that the adiabatic efficiency coefficient reaches its maximum value after the 14th array (the array with the dilution hole) in the 29array plate. Tarchi et al [22]…”
Section: Introductionmentioning
confidence: 99%
“…They highlighted that lower streamwise injection angles perform better to obtain a higher film cooling effectiveness. Tarchi et al [7] investigated the effects of large dilution holes. These holes were placed within the injecting slot and eruption array.…”
Section: Introductionmentioning
confidence: 99%